2010
DOI: 10.1002/chem.200902796
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzo‐ and Naphthoquinonyl Boronic Acids: Exploring the Diels–Alder Reactivity

Abstract: Substituted 2-quinonyl boronic acids have been synthesised from 1,4-dimethoxy aromatic derivatives in two steps: regiocontrolled boronation and oxidative demethylation. The study of their dienophilic behaviour evidenced that the boron substituent significantly increases the reactivity and triggers an efficient domino process in which the Diels-Alder reaction was followed by a protodeboronation or dehydroboronation, depending on the substitution on both the quinone and diene partners. The boronic acid acts as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…Substituted cyclohexene-1,4-diones and derivatives are found in a variety of bioactive natural products and serve as excellent substrates for further synthetic elaboration. Recently, our group reported the synthesis and Diels−Alder reactions of 2-quinonyl boronic acids . Our study evidenced a dramatic increase of their dienophilic reactivity when compared with other reactive quinones, opening an easy access to otherwise elusive adducts, after a domino sequence of cycloaddition and protodeboronation.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Substituted cyclohexene-1,4-diones and derivatives are found in a variety of bioactive natural products and serve as excellent substrates for further synthetic elaboration. Recently, our group reported the synthesis and Diels−Alder reactions of 2-quinonyl boronic acids . Our study evidenced a dramatic increase of their dienophilic reactivity when compared with other reactive quinones, opening an easy access to otherwise elusive adducts, after a domino sequence of cycloaddition and protodeboronation.…”
mentioning
confidence: 73%
“…The most general FC reaction of heteroaryl aromatic derivatives with our 3-methyl substituted 2-quinonyl boronic acids 1 , 9 , 13 , and 20 proceeded by nucleophilic attack of the heterocyclic compound at the C3 methyl substituted carbon. The boronic acid seems to be essential to trigger the process, since no reaction was observed between the pinacol ester derived from boronic acid 1 and indole 4a (CH 2 Cl 2 , rt, 5 d), under the conditions where the free boronic acid 1 reacted in 2 h. Moreover, the boron lacking 2,6-dimethylbenzoquinone was recovered unchanged when treated with indole 4a under the same reaction conditions after long reaction times. These observations suggested that the enhanced electrophilicity of the quinonyl boronic acid must be a combination of the electron-withdrawing effect of the B(OH) 2 group, which decreases the LUMO energy of the C(2)C(3) quinonic double bond, thus decreasing the HOMO−LUMO energy gap, and the existence of a hydrogen bond between the boronic acid and the C-1 carbonyl group (see 1 in scheme of Table ), evident in the X-ray of quinone 1…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Our preliminary work in this area showed that the Dötz benzannulation reaction could be exploited to access quinone boronic esters in good yield and with excellent levels of regiocontrol 5. As quinone boronic acids can serve as precursors to bioactive quinones,6 and have recently emerged as useful substrates for regio‐ and stereocontrolled Diels–Alder reactions,7 this technique held some significant synthetic potential. However, drawbacks associated with the requirement for a stoichiometric organochromium reagent in the Dötz benzannulation reaction prompted us to search for a transition metal catalyzed approach.…”
Section: Methodsmentioning
confidence: 99%
“…Following on from our work devoted to study the reactivity and synthetic applications of quinones, we report our findings on the reactivity of naphthoquinones with β‐arylpyruvic acid derivatives. To the best of our knowledge, this is the first example of α‐keto carboxylic acids combining their C 3 ‐donor pro‐nucleophilicity with their ability to lose carbon dioxide to generate an acyl intermediate (Scheme ).…”
Section: Introductionmentioning
confidence: 99%